THE ‘NAFS’ (SELF), AS OUTLINED BY EARLY PHILOSOPHERS AND SUFI MYSTICS OF AFGHANISTAN AND IRAN - Shahpesandy, Homayun (Khazanah: Jurnal Studi Islam dan Humaniora, 2020)
The understanding of the self is of paramount significance because as individuals we wonder who we are; where we come from; what the purpose of our life is, and what true happiness and misery entail. Muslim philosophers such as Razi, Farabi and Avicenna as well as Sufi mystics like Sanai, Attar and Rumi believe mankind is composed of an external form or body, and an internal entity, which is one?s true substance, ?nafs?, self, mind or soul. Sufi mystics likewise the Muslim philosophers believe that mankind is a union of mind and body; nevertheless, they consider the physical body is a deception, as the true essence of human consists of his soul that is eternal and divine. They emphasize the immortal nature of the soul, created by God that returns through various stages to be in closer proximity to its Creator. They concur ?although man is not primordial, he is eternal; while his corpus is terrestrial, his soul is divine; and although his essence is mixed with animal and voracious attributes; if he gets rid of his maleficence, man will reach the proximity of God, which represents its ultimate happiness.